Community-based participatory research (CBPR) approaches in vaccination promotion: a scoping review - Yan Zhang; Yao Jie Xie; Lin Yang; Kin Cheung; Qingpeng Zhang; Yan Li; Chun Hao; Harry HX Wang; Qianling Zhou; Angela Yee Man Leung (International Journal for Equity in Health, 2024)
Abstract Background Community-based participatory research (CBPR) is a collaborative research approach that engages academic researchers and community stakeholders as equal partners in all research steps to address community concerns and achieve health equity. The CBPR approach has been widely used in vaccination promotion programmes. However, the elements and steps of CBPR-based programmes varied among studies. The purpose of this scoping review was to synthesize the elements and steps, and establish an implementation framework to guide the utilisation of CBPR approaches in vaccination promotion. Methods This scoping review was performed in accordance with Arksey and O’Malley’s five-stage framework. A systematic search was conducted on a set of electronic databases and grey literature sources. The retrieved articles were screened according to the criteria of CBPR and vaccination promotion, and data were extracted and recorded on a calibrated and predefined form in terms of study characteristics and CBPR components. Two authors worked independently to complete literature search, study selection, and data extraction. A narrative summary was used in categorising characteristics, and the contents of the included studies were summarised through qualitative analysis. Results A total of 8557 publications were initially screened, and 23 articles were finally included. According to the CBPR conceptual model, the elements in each CBPR component specifically for vaccination promotion included (1) the establishment of community–academic partnership (CAP)s, (2) community capacity building by partner training vaccination knowledge, research literacy, and service abilities and skills, (3) development and implementation of community-based intervention and (4) Outcome evaluation. A CAP was established between academic researchers or institutes and eight types of partners, including community service organisation–related non-government organisations (NGOs), health service institution–related NGOs, religious organisations, government agencies, educational institutions, media agencies, business agencies, and community representatives. The maintenance of CAP was achieved with four key strategies, namely, strengthening communication, forming management groups, sharing resources and information, and providing incentives. Twelve studies provided comprehensive insights into the strategies employed for intervention development, utilising either quantitative surveys, qualitative methods or a combination of both approaches. The contents of interventions included health service supports, health education activities, social marketing campaigns, community mobilisation, interactive discussions, vaccination reminders and incentives. As for outcome evaluation, vaccination rate and the effectiveness of interventions were assessed. A considerable increase was observed in 95.7% of the included studies (22/23), and the highest increase (92.9%) was attained after the intervention. An implementation framework was generated to summarise the elements and steps of CBPR approaches for vaccination promotion. Conclusions This review summarised current evidence and generated an implementation framework to elucidate the elements and steps in the development and application of CBPR approaches in vaccination promotion. CBPR approaches are recommended for future vaccination promotion programmes, involving community stakeholders and research professionals, to ensure equitable access to vaccinations across diverse populations.